"Loading, please wait" – Temporality and (bodily) presence in mobile digital communication. (27th April 2020) - Sebald, Gerd
Mobile digital communications, as currently the most complex forms of communication, offer a broad view on the phenomenon of communication. The last ten years have seen the addition of new forms of communication (WhatsApp, Facebook, etc.) and the restructuring of a (growing?) share of traditional communication into digitalized forms. Taking these changes as a guideline, this article examines the concept of communication in its temporality, (use of) technology, and physicality and attempts to adapt this concept to current forms.